Analysis of Marketing Communication Strategy at PT Queen Jaya Property Sumedang - Royani, Solihin; Supriatna, Jajang; Cahyati, Dede (Journal of Bussines Management Basic, 2025)
This study aims to determine how the implementation of marketing communication strategies and how the obstacles and solutions to marketing communication strategies at PT Queen Jaya Property Sumedang. The research method uses a qualitative method with the determination of informants using purposive sampling technique. This research data collection technique through observation, interviews, documentation and triangulation. The results showed that the company has implemented 5 dimensions of marketing communication, namely advertising, public relations, personal selling, and direct marketing. However, the implementation has not been done optimally. The identified obstacles include the reach of advertising on social media that is not yet extensive, the limited variety of sales promotions, the quality and consistency of social media content that needs to be improved, the communication and service skills of salespeople that need to be improved, and online marketing content that is less varied and does not follow the latest trends. The efforts that can be made by PT Queen Jaya Property Sumedang in overcoming obstacles are to expand the reach of digital advertising, develop more creative promotions, consistency of social media content, salespeople to improve communication and service, and create online marketing content that is more varied and in accordance with current trends.